PENGGUNAAN MODUL ELEKTRONIK BERBANTUAN CANVA PADA PEMBELAJARAN TEKS FABEL DI SMP KELAS VII KOTA CIMAHI - Nova Irma Yanti; Enung Nurhayati; Yesi Maylani Kartiwi (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research was motivated by the difficulty of students in understanding learning materials Indonesian especially writing fable texts. Based on the results of observations made by researchers, the causative factors are low learning motivation and the ability to think of students in learning activities. In addition, the use of teaching materials in schools is also still conventional, only using package books. Teaching materials in the form of package books allow teacher center learning-based learning activities or learning carried out in one direction, where educators act as the core benchmark that provides material in learning. Therefore, the need for teaching materials that allow students to learn independently so that learning results are obtained optimally, especially in learning to write fable texts, one of which is teaching materials in the form of electronic modules. The purpose of this study was to find out how students respond to the use of Canva application-assisted electronic modules in learning fable texts in junior high school. The method used is qualitative descriptive with an instrument in the form of a questionnaire. The use of electronic modules was responded very well by students, it can be seen from the final results of data processing that there were 90.22% of responses that stated positive, the highest results were obtained in the third statement with a percentage of 97.71% and the first and fifth statements with a percentage of 96%.